Banking Crises in Latin America in the 1990's : Lessons From Argentina, Paraguay, and Venezuela - Garcia-Herrero, Alicia (Washington, D.C. : International Monetary Fund, 1997)
Recent banking crises in Argentina, Paraguay, and Venezuela suggest that the macroeconomic impact is influenced by the causes of the crisis, the exchange rate regime, the degree of dollarization, and the structure of the banking system. Crises stemming from both macroeconomic and bank-specific causes had the largest macroeconomic impact. Countries with high dollarization and a large share of foreign and government-owned banks maintained a more stable deposit base, at least temporarily, by shifting to dollar-denominated deposits and foreign and government-owned banks. Countries that responded with a rapid, consistent, and comprehensive policy response reduced the negative macroeconomic consequences of their crises.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet